Ethical, Legal, and Social Implications (ELSI) Research: Methods and Approaches. Issue 1 (18th January 2022) - Ogbogu, Ubaka; Ahmed, Natasha
Abstract: The article provides an overview of select methodologies that are commonly used in ELSI ("ethical, legal, and social implications") research. ELSI is a field that focuses on the analysis of the societal implications of cutting‐edge biomedical research and technologies. The article aims to provide an accessible reference on well‐established research methods that aspiring and seasoned ELSI researchers can rely on as a starting point for exploring how to design and conduct ELSI studies. © 2022 Wiley Periodicals LLC.